PENGGUNAAN MODEL CONCEPT SENTENCE DENGAN MEDIA SCRABBLE UNTUK MENINGKATKAN PEMBELAJARAN BAHASA INDONESIA PADA SISWA KELAS I SD.Â - Swastyka, Vrening (KALAM CENDEKIA PGSD KEBUMEN, 2018)
Abstract: Vrening Swastyka. The Use of Concept Sentence Model with Scrabble Media to Improve Indonesian Learning at the First Grade Students of Elementary School. The objectives of this research are to describe the application of concept sentence model with scrabble media and to improve Indonesian Learning in using concept sentence model with scrabble media. This research is collaborative Classroom Action Research (CAR), consisting of planning, implementation, observation and reflection. The subject of this research is 21 students of the first grade at SDN 2 Kutosari in the academic year of 2014/2015. The results of this research show that the use of the concept sentence with scrabble media have been implemented through ten steps and can improve Indonesian Learning at first grade of SDN 2 Kutosari in the academic year 2014/2015. Keyword: concept sentence, scrabble, learning, Indonesian Learning Abstrak: Penggunaan Model Concept Sentence dengan Media Scrabble untuk Meningkatkan Pembelajaran Bahasa Indonesia pada Siswa Kelas I SD. Tujuan penelitian ini adalah untuk mendiskripsikan penggunaan model concept sentence dengan media scrabble dan untuk meningkatan pembelajaran Bahasa Indonesia menggunakan model concept sentence dengan media scrabble. Penelitian ini merupakan penelitian tindakan kelas kolaboratif, tahapannya: perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian ini adalah siswa kelas IB SDN 2 Kutosari tahun ajaran 2014/2015 yang berjumlah 21 siswa. Hasil penelitian menunjukkan bahwa penggunaan model concept sentence dengan media scrabble dilaksanakan melalui 10 langkah dan dapat meningkatkan pembelajaran Bahasa Indonesia pada siswa kelas IB SDN 2 Kutosari Tahun Ajaran 2014/2015. Kata Kunci: concept sentence, scrabble, pembelajaran, Bahasa Indonesia